Risks for Using FeCl3 Under a Submerged Condition, and Different Water Management to Reduce Uptake of Antimony and Cadmium in a Rice Plant - Yang, JiGang; Wu, QianHua; Fan, ZhiLian; Feng, RenWei (Frontiers in Environmental Science, 2021)
Soil pollution by multiple metal(loid)s is a common problem, and it is not easy to synchronously reduce their uptake in crops. Compounds containing iron (Fe) are often used to efficiently remediate soil metal(loid) pollution; however, its associated risks did not receive much attention especially under unsuitable soil water conditions. Pot experiments were set up using an antimony (Sb) and cadmium (Cd) co-contaminated soil treated with a continued submergence condition plus 5, 10, or 20 mg kg−1 FeCl3 (Experiment I), or treated with different water management including submergence, intermittent irrigation, and dry farming (Experiment II). Our results showed that the continued submergence resulted in excessive accumulation of arsenic (As) in different tissues of rice plants even if the soil As background concentration is low. High soil moisture content increased the available concentrations of Sb and As, but reduced that of Cd in rhizosphere soils, which was in line with their concentrations in different tissues of rice plants (Experiment II). Under a continued submergence condition, FeCl3 significantly stimulated As concentration in the shoots, roots (excluded Fe20 treatment), and husks, but reduced it in the grains. FeCl3 reduced Sb concentration only in the roots and grains, and reduced Cd concentration only in the husks, suggesting a limited efficiency of FeCl3 to reduce Cd uptake under a submergence condition. In this study, the dynamic changes of As, Sb, and Cd concentrations in soil solution, their available concentrations in rhizosphere soils, their accumulation in root iron/manganese plaques, and the relationships among the above parameters were also discussed. We suggested that if FeCl3 would be used to remediate the contaminated soils by Sb and Cd, dry farming for a short time is needed to avoid As accumulation, and intermittent irrigation is a potential choice to avoid the excessive accumulation of As, Sb, and Cd in the edible parts of rice plants.